The Effect of Continuous Darkness and Continuous Light on the Reactivity of Smooth Muscles to Drugs in the Rat Vas Deferens - Mahdi, Estabraq M. (AL-Kindy College Medical Journal, 2009)
Background: The vasoconstricting agents: nor-adrenaline and 5- hydroxytryptamine(5-HT) have a stimulant action on smooth muscle contractility of the rat vas deferens.Objective: This study aimed to investigate the effect of exposure to continuousdarkness and continuous light on the contractility of the vasa deferntia smoothmuscles from rats to applied nor-adrenaline and 5-HT.Method: Male albino wistar rats were divided into 3 experimental groups. Group 1:Control animals, were exposed to the ordinary photoperiod each day. Group 2: Ratswere kept in a dark room. Group 3: In a room under a bright artificial light.All animals were killed after 4 weeks.Results: Vasa deferentia preparations from continuous dark group of rats exhibited areduced reactivity with a significant lower maximal response to 5-HT than those fromcontrol rats. The maximal response in the control vasa deferentia preparations werenearly doubled compared with that of the continuous dark preparation where as theyresponded to exogenous nor-adrenaline with no significant difference from those ofcontinuous dark animals. Vasa deferentia of continuous light animals responded withdecreased reactivity and a smaller maximal response to both vasoconstrictorscompared with that of control animals.Conclusion: It is concluded that changes in the rhythm of the photoperiod haveconsiderable effects on the reactivity of the vasa deferentia smooth muscle from ratsto applied nor-adrenaline and 5-HT